The Management of Thai Traditional Medicine Services in Health Services to Anti-Aging in Bangkok Metropolitan Region - Chaisuvan, Chaninya; Chantachon, Songkun (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
The objectives of this research were to: 1) study the problems of Thai Traditional Medicine service for Anti-Aging at health service centers. 2) The Management of Thai traditional medicine used in anti-aging at health service centers in Bangkok Metropolitan Region. The research was conducted by using the qualitative participatory research method. The sample group includes 2 public health centers, 9 private health centers, 2 public health service administrators, 7 private health service administrators, 2 doctors, 5 traditional doctors, 10 public health service providers, 140 private health service providers, and 69 patients from health services. The methods used to collect data include observations, interviews, questionnaires, focus group discussions and workshop. The collected data were analyzed by data analysis triangulation procedure, and the analyzed data were then presented through the research method of descriptive analysis. The researches to 1) the problems of anti-aging services with Thai traditional medicine in the health services in Bangkok Metropolitan Region areas have found that personnel are the primary problems – from short-handed, knowledge and ability inequality, and indiscipline. The secondary problems are in the lack of equipment in the public health centers, insufficient parking lot, and lack of registry system and patients’ medical records in private health centers. 2) The Management of Thai traditional medicine in the health services for anti-aging in Bangkok Metropolitan Region area can be categorized into 3 categories. Firstly, the places, internal and external decorations, the area distributions, brightness, appropriated temperature. Secondly, the environment and convenience which include good location, beautiful landscape, sufficient parking lot. Thirdly, the services which include varieties and quick servicing, skillful personnel, ease of contact, and good governance principle. By using this management, the service centers will directly affect the patients in the beneficial and provide happiness.